Geographic variation of the fox Lycalopex culpaeus (Mammalia, Canidae) in Chile: taxonomic implications - Guzmán, Jonathan A.; D’Elía, Guillermo; Ortiz, Juan Carlos (Revista de Biología Tropical, 2009)
We studied the geographic variation of skulls of Lycalopex culpaeus using qualitative and quantative analyses. The sampling area covered Chile, from its northern portion, to Tierra del Fuego and the neighbouring Hoste Island, as well as part of Argentina. Five subespecies are currently recognized from this large area. We found two morphotypes that are segregated geographically. Both groups mostly differ by morphometric attributes, followed by qualitative features. Specimens from northern Chile (Tarapacá and Antofagasta) have small skulls, short rostrum, a liriform sagital zone, and lack the interparietal crest. The second group is formed by specimens from north-western and central Argentina, central-south Chile, Patagonia, and the austral islands of Tierra del Fuego and Hoste. This group presents a strong sagital crest, large rostrum, and a large skull. Our results agree with observed patterns of mitochondrial DNA variation. We propose to retain the name L. c. andinus for the populations of northern Chile and to synonymize L. c. magellanicus, L. c. lycoides, and L. c. smithersi under L. c. culpaeus.